Differential Expression of Tyrosine Hydroxylase Protein and Apoptosis-Related Genes in Differentiated and Undifferentiated SH-SY5Y Neuroblastoma Cells Treated with MPP+. (8th November 2015) - Khwanraj, Kawinthra; Phruksaniyom, Chareerut; Madlah, Suriyat; Dharmasaroja, Permphan
Abstract : The human neuroblastoma SH-SY5Y cell line has been used as a dopaminergic cell model for Parkinson's disease research. Whether undifferentiated or differentiated SH-SY5Y cells are more suitable remains controversial. This study aims to evaluate the expression of apoptosis-related mRNAs activated by MPP + and evaluate the differential expression of tyrosine hydroxylase (TH) in undifferentiated and retinoic acid- (RA-) induced differentiated cells. The western blot results showed a gradual decrease in TH in undifferentiated cells and a gradual increase in TH in differentiated cells from days 4 to 10 after cell plating. Immunostaining revealed a gradual increase in TH along with neuritic outgrowth in differentiated cells on days 4 and 7 of RA treatment. For the study on cell susceptibility to MPP + and the expression of apoptosis-related genes, MTT assay showed a decrease in cell viability to approximately 50% requiring 500 and 1000  μ M of MPP + for undifferentiated and RA-differentiated cells, respectively. Using real-time RT-PCR, treatment with 500  μ M MPP + led to significant increases in the Bax/Bcl-2 ratio, p53, and caspase-3 in undifferentiated cells but was without significance in differentiated cells. In conclusion, differentiated cells may be more suitable, and the shorter duration of RA differentiation may make the SH-SY5Y cell model more accessible.